Use of mental health services in the aftermath of COVID-19 waves: a retrospective study conducted in a French Psychiatric and Neurosciences University Hospital - Anne Perozziello; Daniel Sousa; Béatrice Aubriot; Valérie Dauriac-Le Masson (BMJ Open)
Objective The COVID-19 pandemic and the restrictive measures taken to prevent its propagation had profound effects on mental health and well-being, especially in children and young adults (<25 years old). This study aimed to analyse the medium and long-term impact of the COVID-19 pandemic on the use of the mental health services, by age groups and gender.Design We conducted a retrospective study using the medical and administrative information system databases of patients, between 2019 and 2021.Setting This study was conducted in the Groupe Hospitalier Universitaire Paris Psychiatry and Neurosciences.Outcome measures We reported three indicators: the number of new patients attending outpatient clinics, the number of emergency department (ED) visits and the number of hospital admissions.Methods We considered the weekly number of each indicator, by age groups and by gender. We also collected the reasons of ED visits and hospital admissions. The 2020 and 2021 data were compared with the same period in 2019. The evolution of the indicators over the 3 years was analysed with interrupted time-series analysis.Results All three indicators showed a dramatic decrease during the first lockdown period (March 2020) especially for the youngest. In 2021, the activity resumed but without reaching its prepandemic level. Moreover, mental healthcare seeking was significantly lower since the beginning of the pandemic compared with the prepandemic period for all age groups, except for young women (<25 years old). Among them, there was a higher level of mental health services use in 2021, compared with 2019: +20% of new patients at the outpatient clinics, +39% of ED visits and+17% of hospital admissions.Conclusions The COVID-19 pandemic has had severe consequences on populations’ mental health, especially among young women, which seem to persist months after the end of restrictive measures.